Implementasi Pengelolaan Sampah Ramah Lingkungan untuk Mewujudkan Kota Kupang yang Berkelanjutan Berdasarkan Perda Nomor 3 Tahun 2011 - Haning, Paul Imanuel M; Pello, Jimmy; Yohanes, Saryono (Universitas Proklamasi 45, 2025)
The purpose of this research is to determine and analyze the implementation of an environmentally friendly waste management system in Kupang City based on Kupang City Regional Regulation Number 3 of 2011 and to identify the obstacles faced in implementing the waste management system in Kupang City. Data collection techniques were carried out through document studies and in-depth interviews with related parties, especially the Kupang City Environment and Sanitation Service (DLHK). The results of the study indicate that the implementation of the waste management system in Kupang City has not been running optimally due to various obstacles that can be grouped into three aspects, namely: (1) legal aspects, in the form of the absence of implementing regulations and weak law enforcement; (2) sociological aspects, in the form of low public awareness, participation, and compliance; and (3) institutional and governmental aspects, in the form of limited facilities and infrastructure, weak institutional roles, and minimal coordination between Regional Apparatus Organizations (OPD) and waste management partners. To overcome these obstacles, efforts are needed in the form of strengthening the legal aspects through the preparation of technical regulations, increasing public awareness through education and community involvement, and strengthening institutions and governance.